Woolly hair nevus associated with epidermal nevus of the scalp. - Chieco, P.; Milano, A. (European Journal of Pediatric Dermatology, 2014)
Case report. We visited for the first time a 5-year-old girl because the mother noted from about 6 months a tuft of curly and light hair as compared with the rest of hair that was smooth and brown. The older sister of the patient had a minimal capillary malformation affecting the trunk and right lower limb. The dermatological examination highlighted a tuft of fifteen brown and curly hairs with woolly appearance, while the rest of the hair was smooth and darker (Fig. 1, 2). Moreover, pushing the hair we noticed that the tuft of woolly hair originated from a 2 x 1 centimeter plaque, slightly above the top of the head, of brown-yellowish color, raised for half a millimeter, with an irregular, warty surface (Fig. 3). These peculiar clinical features led us to diagnose woolly hair nevus associated with epidermal nevus of the scalp.